Produksi Bahan Kering dan Kadar Nutrien Indigofera zollingeriana di Lahan Gambut Berdasarkan Umur Panen Berbeda Setelah Pemangkasan: Dry Matter Production and Nutrient Content of Indigofera zollingeriana on Peatland Area Based on Different Harvesting Age after Trimming - Dr. Arsyadi Ali, S.Pt., M.Agr.Sc; R Artika; R Misrianti; E Elviriadi; M M Poniran (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
This study aimed to determine the increase of dry matter production and Nutrient changes of Indigofera zollingeriana cultivated in Sapric peat soils with harvest age of 2, 3 and 4 months after pruning. Indigofera foliage was obtained from the existing plot of approximately 3 years old that grown in the experimental field of the UARDS Laboratory of the Faculty of Agriculture and Animal Sciences of UIN Suska Riau. The research design of randomized block design (RBD) was apllied consisting of 3 age treatments with 4 group. Each treatment, consisted of indigofera biomass harvested at 2 months old (2M), 3 months old (3M) and 4 months old (4M). The results showed that postponing harvest from 2 months to 4 months significantly (p<0.05) increased dry matter production of 71.97 g to 437.62 g and significantly (p<0.05) decreased crude protein (CP) content from 27.45% to 21.23%. Meanwhile, crude fibre (CF), extract ether (EE), ash and nitrogen free extract (NFE) contents were not influence by postponing harvest from 2 to 4 months. The respective ranges of CF, EE, ash and NFE content of I. zollingeriana were CF: 15.50%-16.50%, EE: 2.11%-2.85%, ash: 7.55%-8.31% and NFE: 46.39%-51.15%. It can be concluded that the dry matter production of I. zollingeriana that grown on Sapric peat soils were significantly influenced by harvest age. Key words: legume, maturity, nutritive value, peatland